La gamificación, factor esencial en el aprendizaje de estudiantes universitarios - Coello Contreras, Renato (2024)
The teaching-learning processes are the central axis of the teaching methodology in the different educational contexts. Teacher training at the Higher Education level has a number of disadvantages, including the lack of appropriation of methods consistent with the level and complexity of the challenges that the world of work demands today. The objective of this study is to carry out a systematic review of the academic-scientific literature developed, and to identify the value of gamification as a vital method for greater effectiveness in the acquisition of significant learning in university students. On the other hand, the study proposed the application of surveys to recognize the points of view of teachers and students regarding the use of tools that have gamified characteristics, as well as a comparative analysis of the qualifications obtained from a sample of students in their last semester. taking into account the teaching exercise with gamified and non-gamified tools. The results of the research established that the use of gamified tools enhances the interest of the students, increasing their willingness to acquire curricular academic content and consolidating significant learning, which will allow the development of skills in a practical way, helping them to improve your academic performance and generate a direct impact on job development.